Analisis Strategi Pemasaran Dalam Rangka Revitalisasi Wisata Kerandangan dan Mangsit Kabupaten Lombok Barat - Pratama, Lalu Sulfandi; Permadi, Lalu Adi (Universitas Mataram, 2024)
This study aims to analyze and identify marketing strategies in the context of revitalizing Senggigi tourist destinations, especially in Kerandangan Hamlet and Mangsit Hamlet, West Lombok. The type of research used is descriptive research with a mixed method approach that combines quantitative methods and qualitative methods. The population in this study is people who have visited the tourist destination of Senggigi, especially to Kerandangan Hamlet and Mangsit Hamlet with a sample of 100 respondents. Data collection techniques in this study are observation methods, interview methods, questionnaire methods, literature study methods, documentation methods. The data analysis techniques used in this study are quantitative descriptive analysis, qualitative descriptive analysis and SWOT analysis. The results of the analysis show that the strategy needed for Kerandangan and Mangsit tourist attractions is to grow and build or in other words grow and build. Market strategies that can be done are product development in the form of environmental education tours and maximizing promotional activities for experiences gained while in the region and partnering with local communities.